Distributive Features of Dissolved Organic Carbon in Aquatic Systems in the Source Area of the Yellow River on the Northeastern Qinghai–Tibet Plateau, China - Ma, Qiang; Jin, Huijun; Wu, Qingbai; Yang, Yuzhong; Wang, Qingfeng; Luo, Dongliang; Huang, Yadong; Li, Yan; Li, Xiaoying; Serban, Raul D.; Liang, Sihai; Gao, Shuhui; et al. (Frontiers in Earth Science, 2022)
Dissolved organic carbon (DOC) is a main participant in carbon cycles through water pathways. Recent studies have highlighted the roles of aquatic systems in landscape and watershed carbon budgets. This study is based on 261 samples collected between 2016 and 2017, from individual water types (e.g., river/stream, lake/pond, icing/spring, snow/rain, groundwater/ice, and others) in the Source Area of the Yellow River (SAYR). These samples were analyzed for examining the distributive features of DOC in aquatic systems, especially in relation to environmental factors. It shows that: 1) DOC concentrations in permafrost-related waters (7.2–234.4 mg C·L-1) were often the highest among all aquatic DOC sources (lakes/ponds: 21.3±34.1 mg C·L-1, rivers/streams: 4.3±3.7 mg C·L-1, and groundwater: 1.8±1.4 mg C·L-1); 2) Seasonality of riverine DOC showed declining features in 2016 and high in summer/autumn, followed by a spring freshet in 2017, and a close association with intra-annual precipitation modes; 3) The main controls of aquatic DOC are permafrost presence, precipitation, and NDVI, and; they contribute to 38% of variances of environmental variables in affecting variations in aquatic DOC in the SAYR , and; 4) Literature review on biodegradable DOC (BDOC) of varied aquatic DOC pools indicates the highest DOC concentrations (48–1548 mg C·L-1) and BDOC (23%–71%) of ground-ice meltwater. Thus, we suggest herewith that in the SAYR permafrost dynamics dominate aquatic DOC distribution, and permafrost thaw may alter aquatic DOC budgets, eventually becoming an additional source for atmospheric carbon emissions.